Change of descending aortic false lumen after repair of type I dissection by De Bakey - Chernyavskiy, A. M.; Alsov, S. A.; Lyashenko, M. M.; Sirota, D. A.; Khvan, D. S. (Patologii͡a︡ krovoobrashchenii͡a︡ i kardiokhirurgii͡a, 2015)
Group of authors analyzes the state of thoracoabdominal aorta after reconstruction of ascending and arch of aorta. Currently, there is no single point of view on the amount of interference in the ascending part and the aortic arch in preventing complications of thoracoabdominal aorta. In a group of 46 patients the authors by means of issuing a series of multislice computed tomography, performed at different times after surgery and examine the status thoracoabdominal aorta at different levels. Based on the results of the study revealed that, under the first phase of the surgery department at the ascending aorta and arch over her bundle for DeBakey type I, there is no need to take in a false lumen in the descending thoracic aorta, as it not only does not reduce or slow dilation thoracoabdominal aorta in the long-term, but it is a more rapid increase in comparison with patients with a false lumen was. Saving or suturing the false lumen does not affect the incidence of thrombosis in late postoperative period, and therefore, closure of a false channel in the first phase of intervention is inappropriate.